Atonal homolog 1 is a tumor suppressor gene. - Wouter Bossuyt (Public Library of Science (PLoS), 2009)
Colon cancer accounts for more than 10% of all cancer deaths annually. Our genetic evidence from Drosophila and previous in vitro studies of mammalian Atonal homolog 1 (Atoh1, also called Math1 or Hath1) suggest an anti-oncogenic function for the Atonal group of proneural basic helix-loop-helix transcription factors. We asked whether mouse Atoh1 and human ATOH1 act as tumor suppressor genes in vivo. Genetic knockouts in mouse and molecular analyses in the mouse and in human cancer cell lines support a tumor suppressor function for ATOH1. ATOH1 antagonizes tumor formation and growth by regulating proliferation and apoptosis, likely via activation of the Jun N-terminal kinase signaling pathway. Furthermore, colorectal cancer and Merkel cell carcinoma patients show genetic and epigenetic ATOH1 loss-of-function mutations. Our data indicate that ATOH1 may be an early target for oncogenic mutations in tissues where it instructs cellular differentiation.